New Records of Graphidoid Graphidaceae (Lichenized Ascomycota: Ostropales) for India from the Andaman and Nicobar Islands - Singh, Pushpi; Jagadeesh Ram, T. A. M.; Singh, K. P. (Indian Forester, 2018)
No Abstract.